Assessment of Primary School Teachers’ Knowledge about Stuttering of School-Age Children at First Al-Karkh Education Directorate in Baghdad City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): To assess knowledge of primary school teachers’ about the stuttering of school-age childrenat first al-karkh education directorate in Baghdad city, and find out the relationships between primary schoolteachers’ knowledge and their demographic characteristics.Methodology: The study started from the period of 20th September 2018 to the 1st of March 2020. Probabilitysamples of 370 primary school teachers were chosen randomly. The questionnaire was designed andcomposed of two parts: the first part deals with the teachers’ demographic data; the second part includes astuttering knowledge scale. Determined reliability of the questionnaire through a pilot study and determinedvalidity through a panel of (31) experts. The data was collected through the self-administration methodwas used by asking the participants to complete the format of the questionnaire and fulfill the questions,and it described statistically and analyzed through the use of descriptive and inferential statistical analysisprocedures. Results: The findings of the present study indicate that (53.5%) of the study sample have poor knowledgeabout stuttering of school-age children, and the no-significant relationship between teachers’ demographicalcharacteristics and their knowledge about stuttering.Conclusions: The study concludes that most of the teachers’ had poor knowledge about the stuttering ofschool-age children, and there are no effects of socio-demographic characteristics of teachers’ on theirknowledge about stuttering.Recommendations: The study recommended an education program for primary school teachers aboutstuttering to improving their knowledge about stuttering in the school environment.